Associations between hair cortisol and subjective stress measures in a large occupational sample - Planert, Jari; Klucken, Tim; Finke, Johannes B.; Paulus, Philipp C.; Fischer, Joachim E.; Gao, Wei; Stalder, Tobias (Psychoneuroendocrinology, 2023)
Background - Hair cortisol concentrations (HCC) are commonly used to capture long-term cumulative cortisol secretion in stress research. However, data on associations between HCC and subjective stress measures have been inconsistent. This may partly be due to bias introduced by smaller-sized academic samples. Here, we investigate associations between HCC and (work-) stress-related measures in a large occupational, predominantly male, sample. - Methods - Demographic, anthropometric, and self-reported data were collected as part of an occupational health assessment for employees of an airplane manufacturing company (N = 1258). Hair samples (3 cm) were obtained and glucocorticoid concentrations (HCC and hair cortisone, HairE) were analyzed using liquid chromatography-tandem mass spectrometry. - Results - HCC and HairE were unrelated to self-report measures of perceived stress, work-related stress (effort-reward imbalance, overcommitment), and other stress-related constructs. Group-based analyses concerning associations with job strain revealed a small effect of individuals with high job strain (n = 281) exhibiting higher HCC than the remaining sample (n = 811). - Conclusions - Our data replicate previous findings of no consistent associations between hair glucocorticoids and subjective stress-related questionnaire data, besides evidence for elevated HCC in a high job strain group. Further research addressing open methodological questions regarding HCC by means of advanced stress assessment methods is needed.